(untitled) (Research, Society and Development, 2021)
The microbasins are ideal units for obtaining the characteristics of the landscape, and thus, to properly plan the management of natural resources in agricultural establishments and urban areas. This work aims to characterize the landscape of the Gavião river microbasin, located in the Western Amazon, Brazil. We use the QGIS 2.10.1, Google Earth and TrackMaker Free software, altimetric image from the Alos satellite (Palsar sensor) and equations available in the literature. The Gavião river microbasin has an area of 26.41 km2, perimeter of 32.41 km, elongated shape, altitudes from 207 to 300 m, predominance of flat to wavy reliefs, drainage network of 21.25 km, dendritic pattern of 3rd order, low spring density, medium drainage density, high maintenance coefficient, very straight main channel and concentration time of 2.74 h. We conclude that the microbasin has potential for the development of agriculture, however, it is necessary to adopt soil and water conservation management practices, to mitigate the impacts of anthropic action and guarantee the conservation of water resources.